Questioning power and identity: Race and class in Tambora 1815 by Paox Iben Mudhaffar - Diha, Hamjah; Wahab, Abdul; Zulkarnain, Zulkarnain (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines the discourse of identity politics, focusing on race and class, in local literary texts, specifically in the novel Tambora 1815 by Paox Iben Mudhaffar. Through a cultural studies perspective, the research explores how racial and class identities are represented, constructed, and sustained in local literature, as well as their impact on political and social discourse in Indonesia, particularly in Bima. A qualitative method using literature review and textual interpretation techniques, including repeated reading, data classification, and symbol analysis, was employed, with triangulation for validation. The findings reveal that identity politics in local literary texts can serve as both a tool of resistance against marginalization and a potential source of essentialism and further oppression. The novel reflects and challenges power hierarchies related to race and class, showcasing social inequality and the influence of dominant powers over marginalized groups. This research contributes by providing new insights into the dynamics of power and identity in Indonesian society, offering a critical analysis that encourages further exploration of identity politics in other local literary works